2011
DOI: 10.1007/s00405-011-1696-6
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes: a new non-pharmacological therapy concept for seasonal-allergic-rhinoconjunctivitis

Abstract: Mucosal barrier disorders play an important role in the pathomechanism of the allergic disease. A new approach for their treatment uses liposomes, which consist of phospholipids that make up 75% of the protective nasal surfactant layer. Our aim was to investigate the efficacy of liposomal-based therapy, as a comprehensive treatment alternative to guideline cromoglycate-based therapy, in the treatment of seasonal allergic rhinoconjunctivitis (SAR). We compared nasal and conjunctival symptom reduction with LipoN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…In both treatment groups, 80% of patients perceived the onset of action within 0–2 min after application, resulting in the first perception of relief of allergy symptoms. This finding goes in line with that of an earlier prospective, controlled, open, observational study conducted by Böhm et al [6], which compared a cromoglycate combination therapy to a liposomal nasal spray, either alone or in combination with an LS. They found that 25% of LS users felt an onset of action within 5 min, whereas only 12.5% of cromoglycate eye drop users perceived an onset of action within the same time frame.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In both treatment groups, 80% of patients perceived the onset of action within 0–2 min after application, resulting in the first perception of relief of allergy symptoms. This finding goes in line with that of an earlier prospective, controlled, open, observational study conducted by Böhm et al [6], which compared a cromoglycate combination therapy to a liposomal nasal spray, either alone or in combination with an LS. They found that 25% of LS users felt an onset of action within 5 min, whereas only 12.5% of cromoglycate eye drop users perceived an onset of action within the same time frame.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, previous results from prospective, controlled studies (some of which were randomized and blinded or open-label) suggest that liposomes, in particular in the form of an eye spray, are a promising alternative to standard drug therapy for treating allergic symptoms and should be investigated further [6-12]. Consequently, it was the objective of the present study to gain information on how stabilization of the tear film can influence eye symptoms/irritation during natural allergen exposure in the allergy season.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, early studies using liposomes, which consist of phospholipids that make up 75% of the nasal surfactant layer, have been found to be comparable to cromoglycolate therapy in the treatment of patients with AR (87). In patients with chronic rhinosinusitis associated with cystic fibrosis, expression of SP-A, SP-B, and SP-D is also increased (88,89).…”
Section: Allergic Rhinitismentioning
confidence: 99%